Financial Reporting Practices in Islamic Boarding Schools: Between Traditional Accounting and Indonesian Pesantren Accounting Guidelines - Rahyuni Rahayu; Aulia Loku (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze financial reporting practices at Pesantren S.A.S and examine the implementation of the Pesantren Accounting Guidelines (Pedoman Akuntansi Pesantren/PAP). This research employed a qualitative case study approach using observation, interviews, and documentation techniques. Data were analyzed using interactive analysis consisting of data condensation, data display, and conclusion drawing. The findings reveal that financial reporting practices at Pesantren S.A.S are still dominated by traditional accounting systems focused on recording cash receipts and expenditures. The pesantren has not fully implemented the accounting cycle regulated in the Pesantren Accounting Guidelines, particularly in asset recognition and the preparation of comprehensive financial statements. However, accountability practices are strongly influenced by Islamic values such as amanah and tauhid, which encourage honesty and transparency in financial management. The study concludes that pesantren financial reporting practices currently operate within a hybrid system combining traditional accounting practices and formal accounting standardization efforts.